The First Case of Familiar Anti-leucine-rich Glioma-Inactivated1 Autoimmune Encephalitis: A Case Report and Literature Review - Ding, Chuhan; Sun, Qibing; Li, Ran; Li, Hanli; Wang, Yu (Frontiers in Neurology, 2022)
Anti-leucine-rich glioma-inactivated1 (Anti-LGI1) autoimmune encephalitis is a rare autoimmune disease discovered in recent years. Although the etiology of anti-LGI1 encephalitis is still unknown, it is generally not defined as an inherited disease. Herein, we report the first case of adult patients with familial anti-LGI1 encephalitis. Two biological siblings who worked in different regions were successively diagnosed with anti-LGI1 encephalitis in their middle age. The two patients had similar clinical manifestations, imaging results, and other factors. Their clinical symptoms improved after immunotherapy and antiepileptic therapy. Given that some unique human leukocyte antigen (HLA) subtypes appear at a high frequency, multiple recent studies have revealed that anti-LGI1 encephalitis is associated with genetic susceptibility. One of the patients underwent whole-exome sequencing (WES) and HLA genotyping, which revealed the same HLA typing as in previous studies. However, pathogenic variants were absent in the WES result. Therefore, further studies involving larger samples and more populations should be conducted to explore the possibility of other influencing factors such as environmental impacts.